The utility of certification for managing the state-voluntary sport club relationship: an agency theory perspective. Issue 1 (4th March 2021) - Schlesinger, Torsten; Doherty, Alison
ABSTRACT: Rationale/Purpose: Certification is an institutional mechanism that may, indirectly, have utility for managing the challenges that are likely to be present when the state and voluntary sport clubs (VSCs) connect for sport development. Design/Methodology/Approach: A hermeneutic-dialectic approach guides the adoption of agency theory to conceptualize the state as principal and VSCs as its agents, and to consider agency problems of information asymmetry and divergent interests. Findings: The potential for VSC certification to counter agency problems through harmonization of interests, VSC signaling and reporting of quality and professionalization, state screening and monitoring, and confidence-building through quality assurances, are discussed. Practical Implications: The challenges of certification further inform implications for its indirect application for effectively managing the VSC-state relationship. Research Contribution: The paper advances the limited consideration of both VSC certification and agency theory in the sport literature, combining them for new insights into the potential role of certification for government and community sport relations.